2021
DOI: 10.3390/biomedicines9080883
|View full text |Cite
|
Sign up to set email alerts
|

High Na+ Salt Diet and Remodeling of Vascular Smooth Muscle and Endothelial Cells

Abstract: Our knowledge on essential hypertension is vast, and its treatment is well known. Not all hypertensives are salt-sensitive. The available evidence suggests that even normotensive individuals are at high cardiovascular risk and lower survival rate, as blood pressure eventually rises later in life with a high salt diet. In addition, little is known about high sodium (Na+) salt diet-sensitive hypertension. There is no doubt that direct and indirect Na+ transporters, such as the Na/Ca exchanger and the Na/H exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 143 publications
(276 reference statements)
1
5
0
Order By: Relevance
“…Namely, complete proteome analysis of the brain blood vessel tissue is indicative of an ongoing tissue remodeling process and perturbations in the energy metabolism induced by HSD. This is in accordance with the previous finding of sodium-induced impairment of the endothelial glycocalyx contributing to endothelial cell stiffening and subsequent endothelial dysfunction [44][45][46], as well as the finding of long-term salt loading induced vascular remodeling and cardiac fibrosis in strokeprone spontaneously hypertensive rats [47].…”
Section: Discussionsupporting
confidence: 93%
“…Namely, complete proteome analysis of the brain blood vessel tissue is indicative of an ongoing tissue remodeling process and perturbations in the energy metabolism induced by HSD. This is in accordance with the previous finding of sodium-induced impairment of the endothelial glycocalyx contributing to endothelial cell stiffening and subsequent endothelial dysfunction [44][45][46], as well as the finding of long-term salt loading induced vascular remodeling and cardiac fibrosis in strokeprone spontaneously hypertensive rats [47].…”
Section: Discussionsupporting
confidence: 93%
“…It was found that six weeks of moderate-intensity exercise training reduced the expression of CaMKII and allowed more effective control of glucose homeostasis by improving glucose uptake in adipose and muscle tissue [ 138 ]. Another study reported that a chronically high salt intake induced an increase in intracellular ROS and high CaMKII activity which led to impaired endothelial function [ 139 ]. Studies in obese individuals show that adipocytes have higher intracellular mitochondrial Ca 2+ levels and reduced glucose uptake [ 140 ].…”
Section: Intersection Of the Anti-diabetes Therapy And Camkii Signali...mentioning
confidence: 99%
“…Through integration with various cellular processes, integrins become indispensable in regulating cell functions such as inflammation, proliferation, migration, adhesion, and differentiation. The dysregulation of integrin signaling and conduction can lead to a variety of pathophysiological mechanisms, ultimately contributing to the initiation and progression of CVDs [165]. In the context of AS, integrins can orchestrate plaque formation by promoting EC oxidative stress and inflammation activation, recruiting and promoting the proliferation of VSMCs, inducing calcification, and allowing for the infiltration of immune cells and platelets [15,35,44,62].…”
Section: Discussionmentioning
confidence: 99%